Philippa Foot on Goodness and Virtue (Philosophers in Depth, 2018)
This volume focuses on controversial issues that stem from Philippa Foot's later writings on natural goodness which are at the center of contemporary discussions of virtue ethics. The chapters address questions about how Foot relates judgments of moral goodness to human nature, how Foot understands happiness, and addresses objections to her framework from the perspective of empirical biology. The volume will be of value to any student or scholar with an interest in virtue ethics and analytic moral philosophy.